Magnetic Resonance Imaging for the Follow-up of Treated Thymic Epithelial Malignancies. Issue 6 (November 2019) - Kerpel, Ariel; Beytelman, Arkadi; Ofek, Efrat; Marom, Edith M.
Abstract : Purpose: The purpose of this article was to compare magnetic resonance imaging (MRI) depiction of thymic malignancy progression/recurrence with that of computed tomography (CT). Methods: We retrospectively reviewed all surgically treated thymic epithelial malignancy (TEM) patients between 2011 and 2018 who were followed-up with chest CT and MRI. We compared the detection of recurrence and metastatic disease between the CT and MRI scans in each of these patients. Results: Of 187 patients treated in our institution for TEM, 22 were followed-up with both CT and MRI. TNM stage at diagnosis was as follows: I (n=14), II (n=1), IIIa (n=4), IIIb (n=2), IVa (n=1), and IVb (n=0). Patients were followed-up for a mean of 6.2 years, range 0.7 to 17.7 years. The mean interval between CT and MRI was 5.4 (range, 1 to 15) months. Most patients had no recurrence (n=16), 4 had recurrence after R0 or R1 resection, 1 had stable disease, and 1 had progression of disease after R2 resection. CT and MRI performed equally in the identification of pleural spread (n=5), lymphadenopathy (n=4), and pulmonary metastases (n=1). Retrosternal recurrence (n=1) was identified by MRI despite sternotomy wire artifacts. MRI identified bone involvement and extension of disease into the thecal sac earlier and more readily. Three patients had an indeterminate mediastinal finding on CT that was correctly identified as a benign cyst or pericardial fluid collection by MRI. Conclusion: MRI is an alternative option to follow-up patients after treatment for TEM. However, for those with metallic sternotomy wires, we recommend alternating the follow-up with CT as well.